Perbandingan Kadar Air, Asam Lemak Bebas dan Bilangan Peroksida Pada Minyak Curah dan Minyak Tandusan di Desa Baluk, Jembrana (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2023)
The scarcity of cooking oil in various regions is a significant problem in the food security sector. One alternative that can be done to overcome this phenomenon is to develop Tandusan oil as a product of local wisdom in Baluk Village, Jembrana. The purpose of this study was to determine the water content, free fatty acids, and peroxide number of the Tandusan oil and compare it with the bulk oil on the market. Testing the oil quality parameters uses three samples with the AOAC (Association of Official Analytical Chemists) method. The test results from this study obtained that the water content in the three samples of tandusan oil was 0.16%; 0.12%; and 0.14% while in the bulk oil sample, it was 0.47%; 0.45%; and 0.48%. The free fatty acid content obtained from the tandusan oil test was 0.49%; 0.42%; and 0.46% while in the bulk oil sample, it was 2.39%; 2.41%; and 2.45%. The measured peroxide number in the tandusan oil was 0.52 mg eq/kg; 0.55 mg eq/kg; and 0.50 mg eq/kg whereas in the bulk oil, it is 3.49 mg eq/kg; 3.55 mg eq/kg; and 3.59 mg eq/kg. Tandusan oil has better oil quality than bulk oil and meets SNI 2902:2011 and SNI 3741: 2013 so it is safe to use as food
Keywords: water content; free fatty acids; peroxide number; tandusan oil